Exposure to nano-polystyrene during pregnancy leads to Alzheimer's disease-related pathological changes in adult offspring - Fengxu Wang; Jin Wang; Na Luo; Yonghua Luo; Zhengnan Gao; Ye Cui; Mengna Jiang; Zhaoping Shen; Jing Xiao; Peng Xue; Xiaoke Wang; Shali Yu; et al. (Ecotoxicology and Environmental Safety)
Nanoplastics are common environmental pollutants. As of now, research has yet to explore how exposure to nanomaterials during gestation might influence the risk of developing Alzheimer's disease (AD) in offspring. Throughout the research, we assessed the AD pathology in adult offspring of mice prenatal 80 nm polystyrene nanoparticles (PS-NPs) exposure. In contrast with the control group, prenatal PS-NPs exposure obviously decreased brain tissue weight and the organ coefficient (brain weight/body weight) in adult male mice, but it only led to changes in the low-dose group of female mice. Histological examination of the adult offspring brains revealed alterations following exposure to PS-NPs during gestation. Specifically, there was a substantial reduction in neuron cells, significant changes in the number of Nissl bodies, noticeable loss of cell nucleus, and increased presence of neurofibrillary tangles in adult offspring mice exposed to PS-NPs during gestation. Furthermore, the phosphorylation levels of tau proteins at ser396 and ser199 were dramatically enhanced in the PS-NPs exposed group. Furthermore, the expression of Aβ protein was markedly increased, consistent with typical AD pathological features. Our findings suggest that being exposed to PS-NPs during pregnancy substantially raises the risk of AD in offspring.